Analisis Kepercayaan dalam C2C E-Commerce terhadap Keputusan Pembelian dan Dampaknya terhadap Repurchase pada Kaskus - Prabowo, Hartiwi; Darman, Darman; Noegraheni, Enny (Binus Business Review, 2014)
The development of C2C e-commerce business in Indonesia has grown quite rapidly. This phenomenon is motivated by such a rapid development of the Internet. In the Internet-based commerce transaction, the trust factor (trust) becomes so important because consumers tend to be more concerned if e-commerce merchants do not comply with the obligations of business transactions compared to conventional transaction. This study aims to determine the effect of trust on purchasing decisions and their impact on repeat purchases by customers in the buying and selling forum Kaskus site. The number of respondents are 200 people who have experienced in buying and selling on Kaskus site and this research model is tested using path analysis.The study states that the customersâ trust variable has positive and significant impact on purchasing decisions, the variable purchase decisions has positive and significant effect on repeat purchase and customer trust has positive and significant impact on repeat purchase, but the magnitude of the effect becomes larger after the purchase decision (indirect effect ).